Stig Sjödin's publications in Swedish newspapers: A bibliography - Nilsson, Magnus (Malmö University, 2020)
This excel file lists publications by Stig Sjödin in the Swedish daily press. The main source is Professor Lars Furuland's bibliography in the Swedish Bibliographical Dictionary. However, only those entries have been included that could be verified. In addition, some entries found through new searches in the Swedish daily press are included.

The dataset was originally published in DiVA and moved to SND in 2024.

I denna excellfil förtecknas publikationer av Stig Sjödin i svensk dagspress. Huvudkällan är professor Lars Furulands bibliografi i Svenskt bibliografiskt lexikon. Dock har endast de poster tagits med som kunnas verifieras. Dessutom ingår några poster som hittats genom nya sökningar i svensk dagspress.

Datasetet har ursprungligen publicerats i DiVA och flyttades över till SND 2024.
Stig Sjödins publikationer i svensk dagspress: En bibliografi
Keywords: literary research; litteraturvetenskap; bibliographies (catalogues and directories); bibliografier; personal bibliographies; personbibliografier; General Literary studies; Litteraturvetenskap